Princess Penelopea hates peas : a tale of picky eating and avoiding catastropeas - Sweet, Susan D.; Miles, Brenda; Docampo, Valeria, 1976- (2016)
"Penolopea lives in Capital Pea where peas are plentiful and popular. The problem is that Penolopea hates peas! So she comes up with a plan to make them disappear only leading to a catastropea of epic portions. Eventually, Penolopea grows her own plant and tastes one perfect pea. Turns out, she likes peas after all!"--
"American Psychological Association."
Keywords: Princesses -- Fiction; Food habits -- Fiction; Peas -- Fiction